Identificação de falha na chave inversora do transformador através da análise de gases dissolvidos no óleo mineral isolante - OLIVEIRA, Marcivane da Silva (2019)
This paper proposes the case study carried out in a metal factory in which the production process takes place through self - induction furnaces fed by single - phase transformers. The monitoring of the gas chromatographic analyzes of the oil with the analysis methods used allowed the identification of the root cause of the problem that caused a loss in the transformer A, differentiating the root cause that presented similar results in the transformer B. After the mapping of the facts, corrective and preventive measures were taken to avoid the accident in other transformers. The distinction of a new mode of failure through the mapping of history and analysis of gases is the prevailing theme as a result of this study.